A Challenge to Sustainable Governments? - Keith H. Hirokawa (Washington University Law Review, 2009)
Sustainability, an environmentally-friendly term that previously incited political unrest, economic uncertainty, and even emotional outrage, has become quite commonplace. In federal, state, and local agencies, sustainable practices have dominated dialogues relating to indoor air quality, water availability, energy use and production; but also growth planning and development controls, public spaces and aesthetics. Governmental entities are installing low-flow water fixtures and energy-efficient appliances, redesigning rooftops and skylines, and inviting industry and neighborhoods to the negotiation table to determine the character of future communities. Sustainability has become the vocabulary of politics and is changing those past practices that have become known as resource-wasteful, inefficient, and costly relative to human and environmental needs. Despite the explosion of interest and excitement, many have wondered whether sustainability would find its own limits, or if limitations would be dredged from strategic litigation aimed precisely at identifying both the meaning of sustainability and the nexus between traditional police power authority and a growing awareness of long-term public welfare needs in the natural environment. The point of sustainable practices is not to disrupt existing markets, not to interfere with property rights, and not to place non-human interests above economic ones. Instead, sustainability integrates a comprehensive, "whole systems" analysis of every product, an integration made necessary essentially because we failed to do so in the past. The idea of sustainable industry is persuasive because it is flexible and responsive to new technologies and circumstances. Sustainable practices are likewise persuasive because they are economically, environmentally, and socially superior to the alternatives in the long term. What will make sustainability pervasive, however, is that, in its inclusiveness, sustainable choices are valuable choices.
Keywords: Sustainable development; Green products -- Economic aspects